ORGANIC AND NON-ORGANIC FERTILIZATION OF CASSAVA-BASED CROPS IN NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Cassava is a staple crop in Nigeria, crucial for food security and economic stability. However, its productivity is often limited by soil fertility issues. This study aims to compare the effects of organic and non-organic fertilization on the growth and yield of cassava-based crops in Nigeria. A field experiment was conducted in Rivers State, Nigeria. The study involved 120 plots, each measuring 10m x 10m, divided into three groups: organic fertilisation (compost and manure), inorganic fertilisation (NPK 15-15-15), and a control group with no fertilisation. Data on soil chemical properties, plant growth parameters, and crop yield were collected and analyzed using ANOVA and post-hoc tests. The results showed that organic fertilisation significantly improved soil pH, organic carbon, and total nitrogen levels compared to non-organic fertilization and the control group. Cassava plants in the organic fertilization group exhibited higher growth rates and yields, with an average yield increase of 25% compared to the non-organic group and 40% compared to the control group. Inorganic fertilisation also improved yield but had a lesser impact on soil health, with a notable decrease in soil pH and organic carbon content over time. The study demonstrates that organic fertilization is more beneficial for both soil health and cassava yield compared to inorganic fertilisation. The findings suggest that adopting organic fertilisation practices can enhance sustainable cassava production in Nigeria. Policymakers and farmers should consider integrating organic fertilizers into their farming practices to improve crop productivity and soil health.